Back Cover Image, Volume 1, Issue 3, July 2022. Issue 3 (20th July 2022) - Unknown
Abstract : Back Cover : The fundamental understanding of contact interfaces can accelerate the development of new methods to obtain new fabrication process and to produce triboelectric nanogenerators devices with higher performance. In article number 20220001, Sun et al. give a global overview of the promising strategies towards understanding the differences and similarities of various interfaces based on their structural design.